On the (In)consistency of RE Modeling - Heymann, Carlos Daniel (2018)
Rational Expectations (RE) is typically interpreted as: (i) an equivalence between the probability distribution of future outcomes informing agents´ decisions and the objective distributions; or: (ii) a correspondence between the expectations of agents and those generated by professionally validated models. Both definitions differ, unless absolute validity is counterfactually attributed fallible models built by economists. Another ambiguity arises with the model-consistency notion, since what is considered relevant theory has varied over time and across researchers, especially in Macroeconomics. These issues affect the logic and significance of analytical procedures for treating expectations, and seem particularly pertinent when studying crises.